Optimal integration of distributed generation and conservation voltage reduction in active distribution networks - Quijano, Darwin A. [UNESP] (2019)
Energy efficiency and renewable energy are of paramount importance in the search for a sustainable energy system. This paper investigates the effect of conservation voltage reduction (CVR) on the optimal operation scheduling of active distribution networks with high shares of renewable energy sources (RES)-based distributed generation (DG). To this end, a probabilistic optimal power flow-based algorithm, formulated as a two-stage stochastic programming model, is proposed. In the first-stage, based on forecasts of load demand and DG production, the active power exports and imports, and tap settings of the on-load tap changer (OLTC) and voltage regulators (VRs), are scheduled for the 24 h of the next day. This schedule is optimized to minimize the energy imports and maximize the energy exports. The second-stage simulates the real-time operation of the system for scenario realizations of the uncertainties, and seeks to minimize the energy deficits and maximize the energy surplus once the first-stage decisions have been made. To achieve its objective, the second-stage regulates the DG active and reactive power outputs and coordinates its operation with the OLTC and VRs to reduce the energy consumption through the CVR procedure and maximize the energy harvested from RES, while satisfying system constraints. Results of case studies describe important benefits for energy efficiency, maximum utilization RES, and safe, reliable and economic system operation.